Is truffle brûlé a case of perturbational niche construction? - Bragato, Gilberto (Forest Systems, 2014)
Aim of study: in the context of niche construction theory, the investigation was aimed at assessing if truffle brûlé is a case of niche construction by testing if the disappearance of grasses in the brûlé induces a non-arbitrary perturbation in the soil physical environment and, in that case, which are the physical processes involved. Area of study: a natural truffle bed located in the Italian Apennines inside an experimental truffle-producing area of the University of Perugia. Material and methods: Three aggregate size classes in the soil of a brûlé and of the neighbouring grass-covered area were determined with the wet-sieving technique in accordance with international standards. In the first part of the investigation, the area was sampled according to a systematic sampling design and the spatial patterns of aggregate size classes in the brûlé and in the neighbouring grass-covered area were compared by means of geostatistics. In the second part, the suppression of grasses in the brûlé was mimicked in the laboratory by removing roots from a sample collected in the grass-covered area and the effect of freeze-thaw cycles was tested by comparing a control treatment to other four treatments consisting in sub-samples equilibrated at a water tension of -2.5, -5, -10 and -20 kPa. Samples were submitted to a number of freeze-thaw cycles equal to those recorded in the area, analysed for aggregate size distribution and compared with univariate ANOVA. Main results: The aggregate size classes larger than 0.25mm displayed a spatial pattern comparable to that of the brûlé, with sharp changes along the boundaries of the brûlé itself. The laboratory experiment showed that such changes are attributable to freeze-thaw cycles that in one winter season may produce a significant decrease in aggregate size compared to the grass-covered area. Both results indicate that the disappearance of grasses in the brûlé fulfils the requirement of perturbational niche construction. Research highlights: the observed change of soil aggregation in the brûlé can be useful in delineating soils suitable for truffle farming and in creating suitable soil physical conditions for truffle production by exploiting freeze-thaw cycles after irrigation in winter. Keywords: aggregates; brûlé; niche construction; Tuber, soil structure.